PERANAN ILMU KRIMINOLOGI DAN KRIMINALISTIK DALAM KASUS KEJAHATAN TINDAK PIDANA MUTILASI DI INDONESIA - Berliana, Linaria; Hariyanto, Diah Ratna Sari (Kertha Negara : Journal Ilmu Hukum, 2024)
Writing this journal aims to examine and examine cases of criminal acts of mutilation in Indonesia by using the point of view of criminology, besides that it also aims to determine the role of criminology and criminalistic science in cases of mutilation. The research method used by the author is a sociological juridical research with a qualitative approach. The sources of legal materials used in this study are primary legal materials and secondary legal materials consisting of legislation relating to the issues discussed as well as library sources from articles, media print, newspapers, online media, and previous studies related to the problem, which are then processed and analyzed descriptively to provide an overview of the problems of using knowledge from criminology and criminalism. The results of the criminological study obtained are to identify the modus operandi of the perpetrators, from most cases there is a main mode of the perpetrator mutilating his victim to track and close suspicions, criminology in this mutilation crime case is as an auxiliary science to find out the causal factors, as well as knowing the mode, locus, tempo, and action of the crime of mutilation, which will later show the pattern of the crime making it easier to trace. The role of criminal science in this mutilation crime is to assist investigators in finding evidence of crimes that will later lead to the perpetrators. Keywords: Criminology studies, criminalistics, mutilation, murder